Murdering Truth: 'Postsecular' Perspectives on Theology and Violence. Issue 5 (19th October 2016) - Horner, Robyn
Abstract: While one of the arguments against religious belief relates to its apparent irrationality, it can be shown phenomenologically that there is a different kind of rationality at work in religious knowledge, undermining the sharp distinction between sacred and secular that enables theology to be marginalised as irrational. Approaching Christianity through the category of revelation, that is, as a way of living and believing that draws not only on founding narratives of revelation but on the ongoing 'experience' of transcendence in unveiling truth, I seek to examine how the possibility of truth itself can inspire hatred and so open onto violence. 'Religious' violence typically emerges from a hatred directed at otherness. Hatred of what truth reveals is a powerful motivation for violence, but it cannot be shown that this is specifically religious. Nevertheless, otherness is characterised by an excess that resists objectification and may be revelatory of truth. Violence may be religious precisely to the extent that it is directed against the otherness before which each person stands accused.